2021
DOI: 10.1111/jnc.15378
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin in neurodegenerative dementia

Abstract: Dementia refers to an acquired clinical syndrome in which a person's cognitive level drops significantly, thereby interfering with his/her ability to perform activities related to occupation, family, social interaction, and daily life. The global prevalence of dementia is estimated to be 7% in the population aged over 65 years, with a slightly higher prevalence (8%-10%) in developed countries (due to their longer life spans in such countries) (Jia et al., 2020;Prince et al., 2013). With the acceleration of pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 226 publications
(382 reference statements)
0
21
0
Order By: Relevance
“…39,40 Studies also have shown that PGRN is expressed by microglia and its deficiency may give birth to an aberrant increase in phagocytosis and lysosome function, 39 as well as the transition from homeostatic to disease-specific state of microglia. 41,42 Collectively, these results suggest an important role of PGRN in the modulation of neurodegeneration and neuroinflammatory diseases. Elucidation of the modulating mechanisms of PGRN in the neurodegeneration and neuroinflammation may provide new insight onto the target for the studies on prevention and treatment of these diseases.…”
Section: Discussionmentioning
confidence: 80%
“…39,40 Studies also have shown that PGRN is expressed by microglia and its deficiency may give birth to an aberrant increase in phagocytosis and lysosome function, 39 as well as the transition from homeostatic to disease-specific state of microglia. 41,42 Collectively, these results suggest an important role of PGRN in the modulation of neurodegeneration and neuroinflammatory diseases. Elucidation of the modulating mechanisms of PGRN in the neurodegeneration and neuroinflammation may provide new insight onto the target for the studies on prevention and treatment of these diseases.…”
Section: Discussionmentioning
confidence: 80%
“…It is noteworthy that the distribution of the main bioactive phytochemicals of CR focused in this study is highly specific, such as butylidenephthalide, neocnidilide, senkyunolide A, and Z-ligustilide, which are only present in 3, 6, 10, and 13 herbs, respectively, including CR (data from HERB, http://herb.ac.cn/ ) ( Fang et al, 2021 ). In stark contrast, numerous network pharmacology studies have identified quercetin (related to 341 herbs), kaempferol (related to 248 herbs), luteolin (related to 181 herbs), and β-sitosterol (related to 567 herbs), among others, as candidate phytochemicals for different diseases ( Wang Y. et al, 2021 ; Zhou et al, 2021 ). These widely distributed phytochemicals are highly unlikely to be the herb-specific active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of physiological and pathological tau is mainly mediated by the ubiquitin proteasome system and autophagy/lysosomal degradation pathway. In AD patients, the neuronal lysosome system was dysregulated ( Sundelof et al, 2010 ; Wang X. M. et al, 2021 ; Liu et al, 2021 ; Hamano et al, 2021 ). The results of this study show that CR promotes the degradation of pathological tau mainly through the lysosome system rather than the proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…Progranulin (PGRN) is a secreted protein that is primarily expressed in neurons and microglia in the central nervous system. It demonstrates multifunctional biological functions, including vital roles in inflammation and neurodegeneration disease ( Wang et al, 2021 ). PGRN deficiency promotes neuroinflammation, and it has been a valuable biomarker for frontotemporal lobar degeneration (FTLD).…”
Section: Introductionmentioning
confidence: 99%